2020
DOI: 10.3390/sym12020314
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Exploring the Uniformity of Flow Distribution in Multi-Channels for the Application of Printed Circuit Heat Exchangers

Abstract: The maldistribution of fluid flow through multi-channels is a critical issue encountered in many areas, such as multi-channel heat exchangers, electronic device cooling, refrigeration and cryogenic devices, air separation and the petrochemical industry. In this paper, the uniformity of flow distribution in a printed circuit heat exchanger (PCHE) is investigated. The flow distribution and resistance characteristics of a PCHE plate are studied with numerical models under different flow distribution cases. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In certain areas, owing to the development of the velocity boundary layer, the uneven flow distribution causes some stagnant flowing phenomena, and the fluid preferentially flows to the outer channel (the flow speeds approach to zero; Figure 7A), thus stifling the transport of the heat flux (Figure 7C). The serpentine PCHE is similar to the work, which is done by Ke 50 ; the sudden change of the diameter from inlet to semicircular channel leads to flow separation and nonuniformity. Due to the complex geometry of the S‐shaped channels, the frictional head loss is created, increasing a great pressure drop 51,52 .…”
Section: Resultsmentioning
confidence: 90%
“…In certain areas, owing to the development of the velocity boundary layer, the uneven flow distribution causes some stagnant flowing phenomena, and the fluid preferentially flows to the outer channel (the flow speeds approach to zero; Figure 7A), thus stifling the transport of the heat flux (Figure 7C). The serpentine PCHE is similar to the work, which is done by Ke 50 ; the sudden change of the diameter from inlet to semicircular channel leads to flow separation and nonuniformity. Due to the complex geometry of the S‐shaped channels, the frictional head loss is created, increasing a great pressure drop 51,52 .…”
Section: Resultsmentioning
confidence: 90%
“…To be more specific, when given the value of a random variable, the probability of that value can be calculated from the probability density function, and then the probability density (weight) of that value in all random variables can be calculated. In addition to taking the ordering relationship of the data into account, this method also considers the importance of the data itself [29].…”
Section: Weighted Synthesis Of the Probability Density Function Of Normal Distributionmentioning
confidence: 99%
“…An improved quasi-S-shaped head structure was proposed, effectively reducing heat transfer deterioration due to non-uniformity problems. Ke [19] used a numerical model to study the flow field distribution and resistance characteristics of PCHE plates under different flow field distributions. The results showed that the abrupt change in fluid angle can be greatly reduced by using diffuser plates with equal internal and external radii.…”
Section: Introductionmentioning
confidence: 99%